2022
DOI: 10.1177/23996544221119387
|View full text |Cite
|
Sign up to set email alerts
|

State-led stigmatisation of place and the politics of the exception

Abstract: Ghetto area’ has become an official categorisation in Danish housing policy. This article investigates how this stigmatising spatialisation of politics and policy has emerged through evolving storylines for particular housing estates, which gradually have come to structure political debate and become institutionalised in official policy. While political actors can draw on different storylines, it is argued that a range of storylines and associated quantifiable criteria combine to produce a generic ‘ghetto plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Therefore, through the racial neoliberal urbanism that the Ghetto Package is an example of, we also see how certain ideas are implicit about who is displaceable and who is desirable, which go beyond the specific interventions, so much that nobody even seems to question it: the predominant subject is the White male in all the proposed developmental plans. Now, obviously this rests on previous processes of racialization that goes beyond the specific law as such (as several authors such as Risager, 2022b;Olsen andLarsen, 2022 andSimonsen, 2016 have shown very elegantly), but more importantly, it also goes beyond Danish society and point at tendencies that one might argue are more common for urban planning in general (much like authors such as Giovanni Picker et al, 2019, and Ha and Picker 2022 seem to suggest), but also to the neoliberal Capitalist State in its management of poverty and more importantly the so-called surplus populations (Lundsteen, 2020;Smith, 2011;Soederberg, 2021;Wacquant, 2010).…”
Section: Mjølnerparkenmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, through the racial neoliberal urbanism that the Ghetto Package is an example of, we also see how certain ideas are implicit about who is displaceable and who is desirable, which go beyond the specific interventions, so much that nobody even seems to question it: the predominant subject is the White male in all the proposed developmental plans. Now, obviously this rests on previous processes of racialization that goes beyond the specific law as such (as several authors such as Risager, 2022b;Olsen andLarsen, 2022 andSimonsen, 2016 have shown very elegantly), but more importantly, it also goes beyond Danish society and point at tendencies that one might argue are more common for urban planning in general (much like authors such as Giovanni Picker et al, 2019, and Ha and Picker 2022 seem to suggest), but also to the neoliberal Capitalist State in its management of poverty and more importantly the so-called surplus populations (Lundsteen, 2020;Smith, 2011;Soederberg, 2021;Wacquant, 2010).…”
Section: Mjølnerparkenmentioning
confidence: 96%
“…Until now much literature has focused on the narrative that had been built up during the last decades regarding the failed attempts of the government to integrate what was represented as problematic immigrant ghettos (see Frandsen and Hansen, 2020;Jensen and Söderberg, 2022;Olsen and Larsen, 2022;Seemann, 2021;Simonsen, 2016), and only more recently, authors have engaged with the economic and political interest in privatizing and extending the ongoing processes of gentrification to the corporative housing sector and the entwinement with the previous aspects (see Risager, 2022aRisager, , 2022b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the policy presents a remarkable escalation of the neoliberal pressure to commodify racialized non-profit housing areas. If the early attempts at commodifying non-profit housing were unsuccessful but nevertheless cracked open a door for further commodification, as argued by Larsen and Lund Hansen (2015; see also Vidal, 2019), the 2018 legislation further opened this door, even if it has not (yet) proven to be a 'battering ram' to the non-profit housing sector (see also Olsen and Larsen, 2022).…”
Section: 'Hard Ghettos' and Forced Non-profit Housing Reduction 2018 ...mentioning
confidence: 99%
“…Indeed, many studies have analysed the Danish ‘ghetto’ politics and marginalized housing in general through this conceptual lens (e.g. Birk and Fallov, 2021; Fabian and Lund Hansen, 2020; Fallov and Birk, 2022; Jensen et al, 2021; Jensen and Christensen, 2012; Olsen and Larsen, 2022). While some have highlighted the relation between territorial stigmatization and housing markets (Schultz Larsen, 2014, 2018) or sales (Jensen, 2021), these studies have generally not had non-profit housing commodification as their main concern (see, however, Risager, 2022).…”
Section: Denmark's ‘Ghetto’ Politics and Its Researchmentioning
confidence: 99%